Alternative Medicines in Covid 19 – A Review - K.M.K.masthan1 , E.P. Sridevi Anjuga2 , N.Aravindha Babu3 , E.Rajesh4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Emerging in China in late 2019, the coronavirus disease-2019 (COVID-19) infection epidemic is growingrapidly and new cases are reported around the world. The first cases were linked to a wet market, andsubsequently, the virus has spread rapidly in China through human-to-human transmission, and the universalimpact of the COVID-19 virus is now spreading worldwide. The disease originated from COVID19 is a typeof viral pneumonia that is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2).Currently, no clinically approved antiviral drugs have been introduced for SARS-CoV-2 infection.Identifyingthe mechanism of action of the virus and its interaction with the immune system will help prevent and treatthe disease.There are various researches and studies reporting the use and effect of AYUSH in SARS-CoVtreatment. This review article gives a detailed overview of alternative treatment modalities for COVID 19.